The Stability and Predictability of Betas: Evidence from the Kuala Lumpur Stock Exchange - Mohamad, Shamsher; Md. Nassir, Annuar (Universiti Putra Malaysia Press, 1994)
Beta measures the systematic or undiversifiable risk of a security. Investors desire stable (and hence predictable) measures of beta to enable them to accurately estimate the expected returns on their investment. Instable betas lead to inaccurate estimates of expected returns over time and hence provide misleading signals on performance of investments. This study examines the stability and predictability of the three leads/lags version of FowlerRorke betas (unlike OLS betas, these betas address the problem of thinness of trading peculiar to the KLSE) of 148 firms listed on the Kuala Lumpur Stock Exchange (KLSE). The findings suggest that the beta of both individual securities and portfolios are quite stationary over time. As expected the portfolio betas are relatively more stable than individual securities betas. Furthermore, the method of portfolio formation affects the relative portfolio beta stability. However, portfolio beta stability is achieved with 15 or more securities, irrespective of method of portfolio formation. Overall, the findings indicate that investors can reliably utilize estimated individual security and portfolio betas for their portfolio selection and investment decisions.